Clinical Features of 33 Cases in Children Infected With SARS-CoV-2 in Anhui Province, China–A Multi-Center Retrospective Cohort Study - Zhang, Lan; Huang, Songming (Frontiers in Public Health, 2020)
Background: As of 23rd February 2020, China had 77,048 patients with confirmed SARS-CoV-2 infections, and only 2.1% of patients were under the age of 19 years. Morbidity among Children was much lower, with milder or absent signs and symptoms; chest CT scans showed milder symptoms, if at all, compared to adults. Objective: Report the epidemiological, clinical features, laboratory, radiological characteristics, treatment. Compare additional signs and symptoms, investigate familial clustering, compare laboratory results, find out relevance between age and typical chest CT scans. Methods: We studied 33 young patients with laboratory-confirmed SARS-CoV-2 infection in Anhui Province of China by 16th February 2020. Their signs, symptoms and familial clustering were analyzed. Compare the laboratory test results, compare age and gender among three parts based on chest CT. Results: Familial clustering was seen in 30 (90.91%) patients; 3 families had 7 confirmed members. 24.24% patients had no symptoms, 36.36% had only fever, 27.27% had fever and additional symptoms， and 36.36% had no fever. Dry cough was the most common (44.44%) additional symptom. In 25 patients (75.75%), the percent of lymphocytes decreased; 26 patients were older than 7 years. More male than female patients and older than 8 years, showed typical abnormalities in the chest CT scans (P= 0.038). Only two 18 years old patients had hepatic injury. Conclusion: Children's infection is mild and familial clustering was the most common channel. The older patients had more typical ground glass opacity (GGO) or consolidation in chest CT scans. Cases without fever strongly suggested that non-symptomatic children should not be assumed to be free of infection, when their family members have confirmed infection. Most children showed clinical features distinguished to adult, and with strong epidemic-prone.